2006
DOI: 10.1001/jama.296.19.2329
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Radiotherapy for Pathologically Advanced Prostate Cancer

Abstract: In men who had undergone radical prostatectomy for pathologically advanced prostate cancer, adjuvant radiotherapy resulted in significantly reduced risk of PSA relapse and disease recurrence, although the improvements in metastasis-free survival and overall survival were not statistically significant. Trial Registration clinicaltrials.gov Identifier: NCT00394511.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
569
0
23

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 853 publications
(608 citation statements)
references
References 19 publications
(23 reference statements)
16
569
0
23
Order By: Relevance
“…However, cases with aggressive pathology exhibit high rates of biochemical and clinical disease progression 1. Randomized controlled trials have demonstrated a progression‐free survival benefit for adjuvant radiotherapy (ART) for patients with aggressive pathology after radical prostatectomy, defined by extracapsular extension, seminal vesicle invasion, or a positive surgical margin 2, 3, 4. However, the impact of ART on overall survival is less clear.…”
Section: Introductionmentioning
confidence: 99%
“…However, cases with aggressive pathology exhibit high rates of biochemical and clinical disease progression 1. Randomized controlled trials have demonstrated a progression‐free survival benefit for adjuvant radiotherapy (ART) for patients with aggressive pathology after radical prostatectomy, defined by extracapsular extension, seminal vesicle invasion, or a positive surgical margin 2, 3, 4. However, the impact of ART on overall survival is less clear.…”
Section: Introductionmentioning
confidence: 99%
“…Although many men have relatively indolent disease amenable to active surveillance or definitive local monotherapy, others have more aggressive disease requiring multimodal treatment. Proper risk assessment to identify men at high risk for cancer recurrence, for whom additional treatment may be beneficial [2], is essential to help direct appropriate individualized management.…”
Section: Introductionmentioning
confidence: 99%
“…1 As such, margin status has been incorporated as a component of multiple prostate cancer outcome predictive models, 2,3 and as a criterion for enrollment in adjuvant therapy trials. 4,5 However, as surgical margin status has been linked to other clinicopathological features such as tumor stage, Gleason score, tumor volume and even year of surgery, 1,[6][7][8][9] the independent impact of margin status on patient outcome has been challenged. 10 In particular, the rate of postoperative disease recurrence for patients with a PSM has been reported as between 19 and 50%, reflecting a lack of consistency in the association of margin status with cancer progression.…”
Section: Introductionmentioning
confidence: 99%